ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAHAN (PSAP) NO 13 TAHUN 2015 PADA PENYAJIAN LAPORAN KEUANGAN UNIT PELAYANAN TEKNIS DAERAH (UPTD) PUSKESMAS BAJULMATI DI KABUPATEN BANYUWANGI - Ilma Faizah Wijiyono; Nurshadrina Kartika Sari; Wiwik Fitria Ningsih (RISTANSI: Riset Akuntansi, 2023)
This research was conducted to analyze the application of the Statement of Government Accounting Standards Number 13 of 2015 to the Presentation of Public Health Center Financial Reports as a form of Public Service Agency. This research uses a qualitative method that is descriptive with a case study approach. This study uses in-depth interviews with each informant. The results showed that the Bajulmati Health Center had not implemented PSAP No.13 of 2015 properly and correctly. In its implementation, the presentation of the financial reports of the Bajulmati Health Center uses Banyuwangi Regent Regulation No. 40 of 2018, Banyuwangi Regency Regional Regulation No. 17 of 2107, and Regulation of the Minister of Health of the Republic of Indonesia No. 6 of 2022 in accordance with the directions of the Health Service.